Effect of moisture stress on morpho-physiological parameters of sugarcane ( Saccharum officinarum L.) clones - A.SIV ASANKAR, T . VENU MADHA V , CHA V AN SYAMRAJ NAIK M. VIJA Y KUM AR, J.SURESH and (The Journal of Research, PJTSAU, 2017)
-